Temporal dissonance between group size and its benefits requires whole-of-lifecycle measurements. (4th April 2022) - Hearn, Lucas R; Parslow, Ben A; Stevens, Mark I; Schwarz, Michael P
Abstract: The benefits of living in groups drive the evolution of sociality, and these benefits could vary across a life-cycle. However, there may be experimental problems in linking group size at one time in a life-cycle to benefits that only become apparent later on when group size has changed, leading to what we call "temporal dissonance". In the only known social colletid bee, Amphylaeus morosus, parasite pressures arise at various times throughout the life-cycle from different parasitoid species. Amphylaeus morosus is impacted by eight different parasitoid species operating at different host-colony phenology phases, including five species of Gasteruption wasps, a bombyliid fly and two mutillid wasp species. We found that, as the reproductive season progressed, the number of host adults in a nest declined, often to zero, but the presence of even one adult host female during late brood-rearing stages appeared to offer substantial brood protection against mutillids. We propose that the apparent benefits of colony size at one point in time may not reflect the benefits that become apparent at a later point in the season, leading to a temporal dissonance between group size and its later fitness benefits. We also show that A. morosus is strongly protogynous, with variation in parasitoid pressure across the reproductive phenology distorting operational sex ratios away from initial investment ratios. Combined, our data suggest that seasonal variation in parasitoid pressure may have major consequences for understanding social evolution, but these kinds of consequences are largely unexplored in current studies of insect social evolution. Abstract : The benefits of group living drive social evolution, but these could vary over time and not be evident at all times that group size is measured. We found that important benefits of group size in a primitively social bee are only apparent late in the reproductive season when group size has dwindled and colonies may not even seem to be social. Understanding social evolution requires a whole-of-life viewpoint, and "snapshot" samples may not capture this.